Chloride Resistance Behavior on Nano-Metaclayed Ultra-High Performance Concrete - Mohd Faizal, Md Jaafar; Hamidah, Mohd Saman; Muhd Norhasri, Muhd Sidek; Noorli, Ismail; Nur Farhayu, Ariffin (EDP Sciences, 2017)
Nowadays, the application of nano materials is getting attention to enhance the conventional concrete properties. The ultrafine particles of nano material also will help reducing the formation of micro pores by acting as a filler agent, produce a very dense concrete and will reduce the growth of micro pores in the UHPC structures. The introduction of nano materials in concrete is to increase the strength and durability of concrete. One of the most important factor affecting concrete durability is chloride penetrability. The purpose of this study was to evaluate the chloride permeability and chloride penetration depth by using rapid chloride permeability test (RCPT) and colorimetric method, respectively. The study was conducted for normal performance concrete (NPC), high performance concrete (HPC), ultra-high performance concrete (UHPC) and a series of UHPC (nano metaclayed-UHPC) incorporating different replacement levels of nano metaclay. All the tests were performed at ages of concretes from 3 up to 365 days. The results showed that the presence of silica fume in HPC and nano metaclay in UHPC reducing the Coulombs passed on the 56-days up to 365-days. The experimental results also revealed the depth of chloride ion penetration for nano metaclayed-UHPC concretes are much lesser than those concretes. As regards to the results, nano metaclay led to noticeable benefit in term of chloride resistance.